Promoting psychological adaptability and well-being of patients with personality disorders with creative arts and psychomotor therapies: protocol of an intervention mapping study - Hans Wouters; Jackie Heijman; Suzanne Haeyen; Imke CM Wiersma; Karin Timmerman; Gerben J Westerhof; Mirjam Radstaak (BMJ Open)
Introduction Personality disorders (PDs) cause much suffering. In treating patients with PDs, it is important not only to focus on reducing symptoms, but also on promoting psychological adaptability and well-being. The experiential nature of Creative Arts and Psychomotor Therapies (CAPTs) contributes to working on psychological adaptability and improving well-being, although more evidence is needed. This protocol paper describes a study to develop and evaluate a CAPTs-intervention aimed at promoting psychological adaptability and well-being in people with PDs.Methods and analysis The CAPTs-intervention will be developed using the Intervention Mapping method. A mixed method design will be used for the evaluation of this intervention, using a multiple baseline single case experimental design (MBSCED) with at least 17 participants with a PD included. Quantitative measures that will be completed weekly are the Generic Sense of Ability to Adapt Scale, the Self-Expression and Emotion Regulation in Art Therapy Scale and the Schema Mode Inventory (SMI, healthy adult and happy child). The Mental Health Continuum Short Form, the Brief Symptom Inventory and the SMI (complete) will only be completed at week 1 and 10 of the intervention. Qualitative instruments are an online survey for Experts by Experience, focus groups for CAPTs-therapists, psychologists, managers and referrers, and semi-structured interviews with patients. Quantitative outcomes will be analysed with linear mixed models. Qualitative analysis will be performed using thematic analysis.Ethics and dissemination This study has been approved by the Research Ethics Committee of the HAN University of Applied Sciences (ref: ECO 471.07/23). All participants will sign an Informed Consent and data will be treated confidentially. Study findings will be published Open Access in peer-reviewed journals.Trial registration number This study has been registered at https://www.ClinicalTrials.gov (trial registration number NCT06219122).